Deep Vascular Phenotyping in Patients With Renal Multifocal Fibromuscular Dysplasia. Issue 2 (February 2019) - Bruno, Rosa Maria; Marais, Louise; Khettab, Hakim; Lorthioir, Aurélien; Frank, Michael; Jeunemaitre, Xavier; Laurent, Stéphane; Boutouyrie, Pierre; Azizi, Michel
Abstract : Arterial fibromuscular dysplasia is a nonatherosclerotic, noninflammatory vascular disease, whose pathophysiology is still unknown. We performed deep image-based vascular phenotyping of nonaffected arteries to look for systemic vascular alterations in fibromuscular dysplasia. This single center cross-sectional study included 50 patients with multifocal renal fibromuscular dysplasia, 50 hypertensive patients, and 50 healthy controls, matched for age, sex, and ethnicity; hypertensive patients were matched also for blood pressure. Brachial artery endothelium-dependent and endothelium-independent dilation were studied by echotracking. Aortic stiffness was assessed by carotid-to-femoral pulse wave velocity. We quantified the presence of supernumerary acoustic interfaces within the common carotid wall by the triple signal (TS) score. We plotted the Young incremental elastic modulus/stress curves for common carotid artery, derived from echotracking and tonometry. Patients with fibromuscular dysplasia had impaired endothelium-independent dilation (adjusted P =0.002), smaller brachial artery diameter but comparable endothelium-dependent dilation and aortic stiffness. The prevalence of TS score >6 was 56%, 40%, 24% in patients with fibromuscular dysplasia, hypertensives, and controls, respectively ( P =0.005). Fibromuscular dysplasia remained significantly associated with TS in the multiple regression model ( P =0.022). Impaired endothelium-dependent dilation was present only in patients with fibromuscular dysplasia, TS score >6 ( P =0.047). Incremental elastic modulus was higher for a given wall stress (80 kPa) in the presence of a TS score >6, especially in fibromuscular dysplasia. In conclusion, nonclinically affected large- and medium-sized arteries in patients with multifocal renal fibromuscular dysplasia exhibit a cluster of diffuse alterations in smooth muscle cell function, arterial geometry, wall characteristics, and mechanical properties. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01935752 Abstract : Supplemental Digital Content is available in the text.